When Elites Meet : Decentralization, Power-Sharing, and Public Goods Provision in Post-Conflict Sierra Leone - Clayton, Amanda; Noveck, Jennifer; Levi, Margaret (World Bank, Washington, DC, 2015)
Over the past decade, decentralization of fiscal and policy-making authority has become a cornerstone of development organizations’ recommendations for good governance. Yet the institutional design of multilayered government can create tensions as new elites attempt to fill governing spaces long occupied by traditional patrons. This paper uses the case of post-conflict Sierra Leone to explore the power-sharing dynamics between traditional hereditary chiefs and newly elected community councilors, and how these dynamics affect the provision of local public goods. The paper uses data on several measures of local service provision and finds that councilor/chief relationships defined by competition are associated with higher levels of public goods provision as well as greater improvements in these goods between council areas over time. Relationships defined by frequent contact in the absence of disputes as well as higher frequencies of familial ties between the two sets of actors are associated with worse local development outcomes. This evidence suggests that greater competition between elite groups is beneficial for local development, whereas collusion or cooption between old and new elites harms the provision of local public goods.